MICROCLONAL PROPAGATION OF SPIRAEA JAPONICA FOR LANDSCAPING - Karimova, V.K.; Magzumova, G.K.; Yessimseitova, A.K.; Kakimzhanova, A.A. (Eurasian Journal of Applied Biotechnology, 2021)
Japanese spiraea (Spiraea japonica) is an ornamental shrub widely used in landscaping. The method of clonal micropropagation of Spiraea japonica was optimized to obtain a large number of plants from several shoots. The optimal concentrations of hormones have been established to increase multiplication and root formation. QL medium with 0,5 mg/l benzyl aminopurine (BAP) in combination with 1,0 mg/l gibberelic acid (GA); 0,01 and 1,0 mg/l indolyl butyric acid (IBA); 1,0 mg/l of naphthyl acetic acid (NAA) were tested for multiplication. For root induction, naphthyl acetic acid (NAA) was used in five doses at half the concentration of QL and MS medium. The highest multiplication of shoots (14,02±1,39) and the highest increase in shoot length (6,39) was obtained on QL medium supplemented with 0,5 mg/l BAP; 1,0 mg/l GA and IBA 0,01 mg/l. The highest rooting (100%), the maximum number of roots (6,20±0,63), the length of the longest root (4,60±0,02) was observed on ½ QL medium containing 0,1 mg/l NAA. In conclusion, for Spiraea japonica, an efficient high speed and rooting protocol is described that can be used in mass propagation.